Penerapan Model Webqual: Sebuah Studi Literatur - Uce Indahyanti; Hamzah Setiawan; Nuril Lutvi Azizah (Proceedings Series on Physical & Formal Sciences, 2021)
The functions of a website are very strategic, such as a tool to promote goods and services, display information, and share files or images. In addition, a website is also needed in providing online services to its users, especially during the current pandemic. Because of its very strategic function, many studies have been carried out to measure website user satisfaction using the Webqual model. This study aimed to conduct a literature review on the application of the Webqual model in Indonesia between 2016 and 2020. This study identified the type of website being measured, the data processing techniques used and analyzed the findings. The results of this study indicated that the Webqual model as a measuring tool for website quality could find dimensions and attributes that were positively or negatively correlated with user satisfaction, which could be used as a benchmark in evaluating the quality of the website.